PENGARUH MAKRO EKONOMI DAN PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019-2023 - Soeparyanto, Wiwiek Wiyiastuty; Syaranamual, Irelda Sari (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
This study aims to determine and analyze the influence of macroeconomics (inflation, exchange rates, interest rates, economic growth) and profitability on stock prices of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The population of this study was 42 food and beverage sub-sector manufacturing companies. By using the purposive sampling method, a sample of 14 companies was obtained. The data analysis technique in this study used multiple linear regression analysis. The results of this study indicate that simultaneously, macroeconomics (inflation, exchange rates, interest rates, economic growth) and profitability have a significant effect on stock prices. However, partially, inflation has a negative and insignificant effect, exchange rates have a positive and insignificant effect, interest rates have a positive and insignificant effect, economic growth has a negative and insignificant effect, profitability has a positive and significant effect on stock prices of food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023.